Virtual Environment for the Mashing and Boiling Process in Craft Beer Production - Pogo, Steven (2022)
Process automation allows to increase production and improve the quality of craft products. This paper presents the implementation of closed-loop control algorithms for a mashing and brewing plant of craft beer. The proposed control scheme is implemented through the HIL technique, for which a virtual environment that simulates the behavior of the industrial process and a control card where the control algorithms are implemented are considered. To represent the behavior of the plant level and temperature processes, the mathematical model of each process is obtained, this model is used for the design of the control algo-rhythms, and the plant is modeled in 3D and incorporated into the graphics engine also has effects of realism together with been 3D in order to increase the level of realism to the process. For user interaction with the environment, an HMI type mantle center is incorporated to visualize and control the process manually, semi-automatically, and automatically, in order to test the control algorithms safely and avoid the risk of instrumentation damage or loss of real materials.